Mild activation of the endoplasmic reticulum unfolded protein response conferred cadmium resistance in the nematode Caenorhabditis elegans - Shunchang Wang; Dandan Zhu; Jingjing Wu; Yin Ma; Wenhui Wang; Zhaoxia Chu; Mei He (Ecotoxicology and Environmental Safety)
Cadmium exposure is a major public health concern. Understanding the mechanisms underlying cadmium resistance is crucial for developing preventive strategies and ecological remediation. However, the mechanisms underlying cadmium resistance in animal models remain poorly understood. In this study, we used the nematode Caenorhabditis elegans as a model and found that mild activation of the ER unfolded protein response (UPRER) through tfg-1 RNAi promoted cadmium resistance, and excessive activation of the UPRER resulted in inhibitory effects. Members of the canonical IRE-1/XBP-1 branch, ire-1 and xbp-1, are required for cadmium resistance. Worm strains that constitutively expressed the UPRER reporter were cadmium-resistant, which was abrogated by xbp-1 RNAi. Activation of the UPRER in the insulin/IGF-1 mutated strain daf-2(e1370) enhanced cadmium resistance. Cadmium resistance was abrogated in the daf-16(mu86) mutant strain under UPRER; thus, DAF-16/FOXO bypassed UPRER under cadmium exposure. Activation of UPRER by tfg-1 RNAi stabilized the expression of tryptophan 5-monooxygenase and reduced the aggregation of toxic polyglutamine under cadmium exposure, whereas RNAi against xbp-1 exerted counteracting effects. Taken together, our results demonstrate that mild activation of UPRER promotes cadmium resistance in C. elegans by maintaining protein homeostasis, and that xbp-1 plays a key role in mediating the process.